CASE FRAME AS MEAN OF ORGANIZATION OF COGNITIVE COMPOSITION ACTIVITY OF STUDENTS - V.H. Shcherbyna (Academy of Cognitive and Natural Sciences, 2022)
The prospect of application of organizational case fra m es by development of creative capabilities of students is examined in the article. An author takes the special p la c e f o r model of control after implementation of composition exercises.